Transdiagnostic conceptualization of social avoidance through the lens of personality functioning and traits. Issue 5 (18th May 2021) - Bach, Bo; Eikenæs, Ingeborg Ulltveit‐Moe
Abstract: This commentary seeks to highlight how social avoidance is portrayed in the six presented case‐reports from the perspective of self‐ and interpersonal functioning as well as stylistic trait features of negative affectivity (e.g., anxiousness and shame) and detachment (e.g., social withdrawal and emotional restriction). This approach to avoidance and social isolation will subsequently be generalized to a range of mental disorders where such features play a significant role. We propose that self and interpersonal functioning along with traits of negative affectivity and detachment may serve as a transdiagnostic framework for describing features of avoidance and social isolation across different treatment models, traditions, and disorders. We specifically assume that future developments of the promising treatment approaches presented in the current collection of case reports may benefit from such a "shared" framework for conceptualizing and treating self‐ and interpersonal problems related to avoidance and social isolation.